Religiosity and Anxiety: Evidence From Community Adults During the Crisis Situations - Rini Julistia; Zuhairatul Khairah; Cut Meurah Diza Zuchra; Tri Widia Ningsih; Tsuwaibah Aslamiyah; Mutia Utari; Ade Ira Ramadhan; Amalia; Yola Safira; Sri Ratna Sari; Mandari Putri; Riska Amanti Manik; Elviza Wardani; Jauharatul Qulub; Dara Salsabila; Nursan Junita (Jurnal Psikologi Terapan, 2025)
The COVID-19 pandemic has created a global crisis that affects not only physical health but also psychological well-being, particularly increasing anxiety levels in the community. Various protective factors have been proposed to buffer psychological distress, including religiosity. This study aimed to examine the relationship between religiosity and anxiety among community members during the COVID-19 pandemic. A quantitative correlational design was employed with participants drawn from early adulthood (18–40 years). Religiosity was measured using a multidimensional religiosity scale covering religious belief, religious practice, religious experience, and religious knowledge, while anxiety was assessed using a standardized anxiety scale. Data were analyzed using Pearson correlation analysis and ANOVA-based significance testing. The results showed a significant negative correlation between religiosity and anxiety (r = −.511, p < .01), indicating that higher religiosity is associated with lower anxiety. All four dimensions of religiosity were also negatively correlated with anxiety: belief (r = −.174), practice (r = −.459), experience (r = −.528), and knowledge (r = −.285), all at p < .01. These findings suggest that religiosity functions as an important psychological protective factor in crisis situations. The study contributes to culturally contextual evidence regarding the role of religiosity in reducing anxiety during large-scale public health emergencies